Optimal Combination of Anodal Transcranial Direct Current Stimulations and Motor Imagery Interventions - Elodie Saruco; Franck Di Rienzo; Susana Nunez-Nagy; Miguel A. Rubio-Gonzalez; Ursula Debarnot; Christian Collet; Aymeric Guillot; Arnaud Saimpont (Neural Plasticity)
Motor imagery contributes to enhance the (re)learning of motor skills through remapping of cortical networks. Combining motor imagery with anodal transcranial direct-current stimulation (a-tDCS) over the primary motor cortex has further been shown to promote its beneficial effects on postural control. Whether motor imagery should be performed concomitantly to a-tDCS (over depolarized membrane) or consecutively (over changing neurotransmitters activity) remains to be elucidated. In the present study, we measured the performance in a postural control task before and after three experimental conditions. Participants received a-tDCS before (tDCSBefore), during (tDCSDuring), or both before and during motor imagery training (tDCSBefore + During). Performance was improved after tDCSDuring, but not after both the tDCSBefore and tDCSBefore + During conditions. These results support that homeostatic plasticity is likely to operate following a-tDCS through decreasing cortical excitability and that motor imagery should be performed during anodal stimulation for optimum gains.